Prenatal Attachment Behaviour Counselling in Women With High-Risk Pregnancy After Infertility: Evidence-Based Nursing Practice - Parmawati, Ika; Nur Rachmawati, Imami; Afiyanti, Yati (Talenta Publisher, 2024)
The prevalence of anxiety in pregnant women increases along with high-risk pregnancy conditions. Severe anxiety hurts the mother, fetus, and spouse, including difficulty in achieving prenatal attachment. This study aims to implement evidence-based nursing to reduce anxiety and enhance prenatal attachment in women with high-risk pregnancies after infertility. To achieve these aims, a pilot study was conducted using the Joanna Briggs Institute (JBI) Evidence-based Audit and Feedback as well as Getting Research into Practice (GRiP) approach, consisting of 7 phases, namely identifying areas, involving agents of change, assessing context and readiness, reviewing practices with audit criteria based on scientific evidence, implementing with the GRiP, reassessing with follow-up audits, and considering project sustainability. The study involved 5 women with high-risk pregnancies after infertility. The clients received attachment behaviour counselling, followed by evaluations related to anxiety and prenatal attachment after 7 days of interventions. The result of the study was that all five (100%) women with high-risk pregnancies after infertility experienced a decrease in anxiety and achieved high scores in prenatal attachment. Attachment behaviour counselling effectively decreases prenatal anxiety and enhances prenatal attachment.